Nos caminhos da escola do campo : processo de implantação da educação do campo no município de Matão, SP - Jesus, Adriana do Carmo de (2013)
This paper addresses the contexts and processes regarding the implementation of the education proje Rural education, municipality of Matão and education project of the field.ct within the field of the Municipal Education Matão / SP. The city has three primary schools in the countryside, since the year 2005 work differently from the other three schools of the same level, located in the urban area. Organize educational work from generating themes and themed calendar. In developing the research we assume that to understand the contexts related to the field of education it is necessary to grasp before which the historical conditions of the field and the field worker. The investigation procedures adopted were the records of reports of different subject: Municipal Secretary of Education, principals and teachers of the three schools of the field, we also analyze the documents prepared in order to record the process of discussion and progress in project implementation Field school in the city. Then used to establish the configuration of the field Matão has traits of field configuration in Brazil, which has prevailed in the agroexport model, and with a shortage of workers who live in the countryside. We note that the proposed municipal school field has incorporated some proposals of the movement For A Field Education, and the organization of educational work of these schools is a movement of approach and departure from the hegemonic conception of rural education. Signaled the need to revisit the design of rural schools and invest in continuous training of teachers to better meet the defined objectives.